Analysis of Patients with PCOS According to Demographic Factors & Hormonal Assayin Babylon Government in Iraq (Medico Legal Update, 2020)
Introduction: PCO is asignificant alteration in hormonal state that happen in females which lead to ovulatoryreasonsof subfertility & amenorrhea in reproductive period. Polycystic Ovarian Syndrome was collectingof presenting symptoms and signs.If we had two of the following presenting sign and symptoms,we called this condition as PCO.1. Oligomenorrhea & amenorrhea (menstrual and ovulating problem).2. Signs of hyperandrogenimea (clinical or biochemical).3. U/S features of polycystic ovaries which include (thick stoma on the periphery of the ovaries,whichinclude multiple small follicles > 10and largest one < 9 mm,while the ovarian size > 10 cm3.Aimsof the study :- analysis of Iraqi women in AL- Hilla city who present with problems in her menstrualcycle or fertility and assess their period of age when maximum symptoms and signs were appear,BMI,hereditary factors,occupation, residence, marital status and laboratory investigation to confirm ourdiagnosis (FSH, LH, AMH, PRLACTIN, TESTESTERONE) then vaginal u/s was done for marriedwomen and abdominal u/s done for unmarried one.Patients and Method: Case controlled study carried out for women that suffer from problems in hermenstrual cycle and fertility from outpatient clinic in Babylon teaching hospital and some privet clinics, inperiod of 1year from(June 2017 to June 2018).100 complaining women were participated in this study randomly after verbal and written consent whichtaken from them.Results: 100 women were shared in this study, we observed that percentage of infertility increase at thecurrent time due to PCO for unknown reason, in addition to elevation percentage of PCOS frankly accordingto The Rotterdam criteria(symptoms and signs of presenting women), this multisystimic disorders disturbfertility to large extent because hormonal disturbances such as increase LH\FSH ratio, Prolactin & AMHalso increase ovarian volume due to thick stromal layer of the ovary then we assess affecting factors andrelieving factors, its relation to patients age, BMI, occupation, residence and her hereditary state andhormonal analysis to document the diagnosis.Conclusions: Found fright increase of infertility in couples especially in our country in relative to the past,previously the incidence of infertility is about 12% of total couples and the incidence of PCO in generalfemale about 35%(married or unmarred, may be due to delay discovery especially in unmarried group) &45% in married women decreasing with progress of age.